Ethnic dermatology clinical problems and skin pigmentation - Archer, Clive B. (Informa Healthcare, 2008)
Recognizing the enormous variety of skin diseases in lightly pigmented skin depends on the development of a number of visual skills that have to be developed still further to recognize skin diseases in deeply pigmented skin from different ethnic groups. The comparison of skin disorders in white and deeply pigmented skin is in itself an important way of learning; by using this book regularly, the reader will become familiar with the appearance of common and uncommon skin diseases in people with varying degrees of skin pigmentation. This beautifully illustrated text on ethnic dermatology provides a systematic approach to the diagnosis and management of a wide variety of skin diseases; the second edition has been reorganized and updated to enforce its usefulness for the busy practitioner needing to compare important differences in the way skin diseases manifest themselves.